Smart Eye: An Application for In Situ Accessibility to "Invisible" Heritage Sites. Issue 1 (23rd December 2022) - Efkleidou, Kalliopi; Kaimaris, Dimitrios; Roustanis, Themistoklis; Patias, Petros; Andreou, Stelios; Klimantakis, Kostas; Karolos, Ionas-Anastasios; Pappa, Maria; Kouidis, Nikos
The Smart Eye Application is an augmented reality app for mobile devices that enables the in-situ 3D visualization of underground and inaccessible to the public archaeological sites and monuments. Accessibility to excavated archaeological sites and monuments is often hindered for reasons of preservation or urban development. Portable finds are transferred and, in some cases, exhibited in local museums, but the non-portable remains of ancient structures become eventually effaced from the landscape and the collective memory of local communities. The Smart Eye app provides an "x-ray" type view of excavation sites that have been backfilled and are now invisible. While common practice in heritage sites' digital dissemination to the general public uses 2D or 3D reconstructions in augmented or virtual reality environments, the Smart Eye app presents archaeological remains in the shape and form they were found in by archaeologists supplemented with augmented reality markers that provide simplified textual and visual information aimed toward a non-scholarly public. The aim is to re-instate these heritage sites into the interactive relationship that people have with their landscape and their history. The present paper discusses the chaîne-opératoire of developing the app, from the acquisition of primary documentation data of the excavation sites to the methodology used for the production of the 3D models of the archaeological sites and the development of the app itself and the technical equipment used. Finally, we discuss the results of the preliminary evaluation of the application and future steps to improve it before final testing by the local communities where the archaeological sites are located.